Technology, natural resources and economic growth improving the environment for a greener future - Managi, Shunsuke; Edward Elgar Publishing (Cheltenham [England] : Edward Elgar Pub., 2011)
Through a combination of global data analysis and focused country level analysis, this timely book provides answers to the most pertinent country and industry specific questions defining the current relationship between technology, natural resources and economic growth.
pt. 1. Global analysis -- pt. 2. Country-level analysis.
Includes bibliographical references and index.
Keywords: Green technology; Environmental protection -- Technological innovations; Conservation of natural resources; Electronic books